2013
DOI: 10.1007/s12603-012-0399-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nucleotides extend the life span in Sprague-Dawley rats

Abstract: Long-term feeding of NTs could dose-dependently increase life span in Sprague-Dawley rats, especially, the tumor-bearing ones. Moreover, the antioxidative property of NTs may be responsible for the increased life span.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 32 publications
4
24
0
Order By: Relevance
“…MDA is one of the degradation products of lipid peroxidation, an important indicator for evaluating cellular oxidative stress [25]. Studies indicated that NTs exhibit remarkable anti-oxidative activities [11,13]. Our results suggested that the anti-fatigue effects of NTs are closely related to the protection of corpuscular membrane by improving the activities of several enzymes and preventing lipid oxidation.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…MDA is one of the degradation products of lipid peroxidation, an important indicator for evaluating cellular oxidative stress [25]. Studies indicated that NTs exhibit remarkable anti-oxidative activities [11,13]. Our results suggested that the anti-fatigue effects of NTs are closely related to the protection of corpuscular membrane by improving the activities of several enzymes and preventing lipid oxidation.…”
Section: Discussionmentioning
confidence: 57%
“…A number of reports have demonstrated that adding NTs to dietary formulas increases the production of immunoglobulins, improves response to vaccines, reduces morbidity, and increases tolerance to dietary antigens [12,14]. Our previous studies found that NTs are not toxic or carcinogenic in rats at a concentration of up to 0.64% (of body weight) for their entire lifetime, and could extend the lifespan in SD rats in a dose-dependent manner [13]. To the best of our knowledge, the present study is the first to report that dietary NTs supplementation improves the fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nucleoprotein may also have antioxidant capacity since dietary nucleotide, a component of nucleoprotein, has been shown the activating antioxidant enzymes in serum of rat (Xu et al. ).…”
Section: Introductionmentioning
confidence: 99%